Amylolysis as a tool to control amylose chain length and to tailor gel formation during potato-based crisp making. (June 2020) - Reyniers, S.; Vluymans, N.; De Brier, N.; Ooms, N.; Matthijs, S.; Brijs, K.; Delcour, J.A.
Abstract: Potato flakes (PFs) are used for producing potato-based crisps. Their cold-water swelling starch instantly binds water during dough mixing. The dough is then sheeted and deep-fried. We here used α-amylase from Bacillus subtilis (BSuA) and Bacillus stearothermophilus (BStA) to unravel the role of PF amylose (AM) during crisp production. Treating PFs with BSuA [30.0 EU/g PF dry matter (dm), 10 min, 40 °C] increased the extractable starch (E-S) content from 8.6 to 42.7% of PF dm but the degree of polymerization (DP) of the E-S chains was lower than 150. Although time domain proton nuclear magnetic resonance (TD 1 H NMR) analysis showed that these enzymatically released starch chains with DP lower than 150 readily crystallize during dough making, they are not able to contribute to formation of strong gels. In contrast, amylolysis of PF starch by BStA (30.0 EU/g PF dm, 10 min, 40 °C) only slightly impacted the E-S content (11.0% of PF dm) but increased the level of relatively short extractable amylose (E-AM) chains [(DP between 150 and 1500 (E-AM150-1 500 )] by 35%. Incubation (10 min, 60 °C) of 7.8% of the PF dm in the dough recipe with the same BStA dosage prior to dough making showed that E-AM150-1 500 chains increase the extent of AM crystallization during dough making (as evidenced by TD 1 H NMR analysis) and thereby strengthen the starchy gel network. As a consequence, expansion of the food matrix during deep-frying was hampered, which increased product hardness and reduced oil uptake by 10% and 8%, respectively. This study is the first to show that the level of AM chains of intermediate length is crucial for the texture of potato-based food matrices. Graphical abstract: Image 1052 Highlights: Amylose (AM) structure determines the strength of potato flake based dough systems. Intermediate length AM promotes crystal formation which strengthens dough sheets. Limited amylolysis increases the level of intermediate length AM chains. Extensively hydrolyzed AM readily crystallizes yet weakens the dough sheet. Strong starch gels limit dough expansion and oil uptake during deep-frying.